2023
DOI: 10.3390/antibiotics12030624
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Antimicrobial-Related Adverse Drug Events in Jordan: An Analysis from the VigiBase Database

Abstract: This study aims to assess the reporting of antimicrobial-related adverse drug events (ADEs) in Jordan between 2003 and 2022. Data regarding the antimicrobial-related ADEs were extracted from the WHO’s global database (VigiBase) by the Rational Drug Use and Pharmacovigilance Department at the Jordan Food and Drug Administration (JFDA). A total of 279 Individual Case Safety Reports (ICSRs) were recorded. The number of ICSRs increased from 2019 onwards (219 out of 279 cases). This increase in the reported ADEs wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In 279 reports, it was possible to characterize the AEs, and the "drug ineffective" MedDRA PT (n = 28; 5.19%) was most often related to carbapenems (n = 9; 32%), followed by tetracyclines (n = 8; 28%). The study also found "off-label" reports (n = 13; 2.41%), "incorrect route of administration" (n = 10; 1.89%), and "unapproved indication" (n = 6; 1.11%) [111].…”
Section: Pv As a Tool To Identify The Ineffectiveness Of Antibioticsmentioning
confidence: 74%
“…In 279 reports, it was possible to characterize the AEs, and the "drug ineffective" MedDRA PT (n = 28; 5.19%) was most often related to carbapenems (n = 9; 32%), followed by tetracyclines (n = 8; 28%). The study also found "off-label" reports (n = 13; 2.41%), "incorrect route of administration" (n = 10; 1.89%), and "unapproved indication" (n = 6; 1.11%) [111].…”
Section: Pv As a Tool To Identify The Ineffectiveness Of Antibioticsmentioning
confidence: 74%
“…In 279 reports, it was possible to characterise the AEs, and the "drug ineffective" MedDRA PT (n = 28; 5.19%) was most often related to carbapenems (n = 9; 32%), followed by tetracyclines (n = 8; 28%). The study also found "off-label" reports (n = 13; 2.41%), "incorrect route of administration" (n = 10; 1.89%), and "unapproved indication" (n = 6; 1.11%) [111].…”
Section: Pv As a Tool To Identify The Ineffectiveness Of Antibioticsmentioning
confidence: 74%
“…Likewise, in a study done by Junk et al in South Korea, the most common antibiotic-associated ADR is cephalosporins (both first and second generation) in 26.1% followed by Penicillin and Quinolone in 16% of the patients [ 10 ]. In a study conducted in Jordan based on the data extracted from WHO global database (VigiBase), 48 patients are recorded for third-generation cephalosporins-mediated ADR, and the commonest antibiotic for the cause of ADR is tetracyclines (n=101), followed by fluoroquinolones (n=54) [ 17 ]. Meanwhile, in a Malaysia study, the second most common cause of ADR is a cephalosporin (20.6%) and the primary cause of ADR is mainly due to penicillins (32%) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Mhaidat et al's study, the most common organ affected as a result of ADR is skin and subcutaneous tissue disorders in 19.48% of patients. Further, they also reported that in ADR related to skin, rashes are the most commonly observed reaction in 58 cases (10.76%) and the incidence of rashes is higher in patients consuming third-generation cephalosporins (n=11, 18.97% out of 58) [ 17 ]. In Jung et al's study, cutaneous and skin-related toxicities are the most common ADR event in 45.1% of cases and cephalosporin accounts for 46.25% of skin-related manifestations [ 10 ].…”
Section: Discussionmentioning
confidence: 99%